Eric Schlosser: Fast Food Nation. What the All-American Meal is Doing to the World - Davidson, Alan E (Petits Propos Culinaires, 2024)
Eric Schlosser: Fast Food Nation. What the All-American Meal is Doing to the World: Allen Lane The Penguin Press, 2001: ISBN 0-713-99602-1, 356 pp., paperback, £9.99.